Assessment of Pesticide Application Pattern in Major Vegetables of Palpa District, Nepal - Sharma, Bala; Ojha, Bishnu Raj; Ojha, Ankit; Sapkota, Bina; Adhikari, Gaurav; Gautam, Samikshya (International Journal of Social Sciences and Management, 2021)
This study was conducted to determine the cost contribution of pesticide to total cost of vegetable production along with criteria for the choice of pesticides, its handling and application pattern. It also includes the amount of pesticides imported in 2020 in Palpa district. Fifty farmers and 15 agro-vets were selected for a pretested questionnaire schedule. Microsoft-Excel and Statistical Package for Social Sciences were used to analyze the data. Mean and standard deviation was used to categorize the age of respondents. Contribution of pesticides was 3% to the total cost of vegetable production. Farmers were rarely aware of safe application procedures, 64% used different pesticides based on their efficacy alone and 54% didn’t adopt any safe disposal mechanism. Among different chemical classes of pesticide used for vegetable production, organophosphates constitute the highest i.e. 80%. Highest annual consumption of organophosphate pesticide was malathion dust (2287 kg) and carbamate was mancozeb (196 kg). Int. J. Soc. Sc. Manage. Vol. 8, Issue-1: 292-298